Understanding deep learning - Prince, Simon J. D. (Cambridge: The MIT Press, 2023)
"This book covers modern deep learning and tackles supervised learning, model architecture, unsupervised learning, and deep reinforcement learning"--
Includes bibliographical references and index.
Keywords: Deep learning (Machine learning)